1999
DOI: 10.1037/0096-3445.128.3.219
|View full text |Cite
|
Sign up to set email alerts
|

The role of phonology in the activation of word meanings during reading: Evidence from proofreading and eye movements.

Abstract: Six experiments explored the role of phonology in the activation of word meanings when words were embedded in meaningful texts. Specifically, the studies examined whether participants detected the substitution of a homophone mate for a contextually appropriate homophone. The frequency of the incorrect homophone, the frequency of the correct homophone, and the predictability of the correct homophone were manipulated. Also, the impact of reading skill was examined. When correct homophones were not predictable an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

13
130
4
3

Year Published

2002
2002
2015
2015

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 125 publications
(150 citation statements)
references
References 41 publications
13
130
4
3
Order By: Relevance
“…The V& b y frequency interaction contributed a significant unique arnount of variance in the prediction of errors in one of the studies. In conjunction with the results of Jared (1997;submitted), this suggests that consistency effects are no t iimited to low frequency words.…”
Section: Consistencv Effects With Monosyllabic Wordssupporting
confidence: 51%
See 3 more Smart Citations
“…The V& b y frequency interaction contributed a significant unique arnount of variance in the prediction of errors in one of the studies. In conjunction with the results of Jared (1997;submitted), this suggests that consistency effects are no t iimited to low frequency words.…”
Section: Consistencv Effects With Monosyllabic Wordssupporting
confidence: 51%
“…First, Treiman et al (1995) found that frequency-byconsistency interaction measures did not predict naming latencies or error rates in their analyses of two mega-studies. Second, Jared (1997) found that spelling sound consistency of the word body affected the naming latencies of high-frequency words when the frequencies of friends and enemies were carefully controlled in the same namrner as for low-frequency words that produced consistency effects. Third, Jared (submitted) replicated her earlier result, and again found that high-frequency words were af'fected by the spelling-sound consistency of their word-bodies.…”
Section: Experiments 3: No Frequency By Consistency Interactionmentioning
confidence: 99%
See 2 more Smart Citations
“…Individual differences on a variety of cognitive tasks have been shown to relate to variability in eye movements during reading (e.g., Ashby, Rayner, & Clifton, 2005;Jared, Levy, & Rayner, 1999;Kuperman & Van Dyke, 2011). A key requirement for explaining the nature of individual differences during reading is to better understand how and why readers differ in their ability to extract visual information from the parafovea and to use this information to make processing more efficient.…”
Section: Introductionmentioning
confidence: 99%